2021
DOI: 10.3390/cancers13163969
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-Related Peptidase 6 Is Associated with the Tumour Microenvironment of Pancreatic Ductal Adenocarcinoma

Abstract: As cancer-associated factors, kallikrein-related peptidases (KLKs) are components of the tumour microenvironment, which represents a rich substrate repertoire, and considered attractive targets for the development of novel treatments. Standard-of-care therapy of pancreatic cancer shows unsatisfactory results, indicating the need for alternative therapeutic approaches. We aimed to investigate the expression of KLKs in pancreatic cancer and to inhibit the function of KLK6 in pancreatic cancer cells. KLK6, KLK7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 44 publications
4
24
2
1
Order By: Relevance
“…Variability could relate also to technical sensitivities (e.g., in silico, qRT-PCR, and ELISA and immunohistochemistry) or to selected tissues (i.e., colon mucosa from healthy donors or paired adjacent mucosa). Indeed, some KLKs are highly expressed at sites of inflammation [ 39 ] and might, therefore, also be elevated both in the immune cells and in the glandular epithelial cells in non-cancer-bearing tissues obtained from individuals with non-diagnostic bowel diseases. In our analysis, we did not detect KLK6 in inflammatory cells and KLK6 staining was restricted to the cancerous mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Variability could relate also to technical sensitivities (e.g., in silico, qRT-PCR, and ELISA and immunohistochemistry) or to selected tissues (i.e., colon mucosa from healthy donors or paired adjacent mucosa). Indeed, some KLKs are highly expressed at sites of inflammation [ 39 ] and might, therefore, also be elevated both in the immune cells and in the glandular epithelial cells in non-cancer-bearing tissues obtained from individuals with non-diagnostic bowel diseases. In our analysis, we did not detect KLK6 in inflammatory cells and KLK6 staining was restricted to the cancerous mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Based on TCGA database analysis, KLK6 is significantly upregulated in 16 cancer types. In addition, the elevation of KLK6 expression has been reported in the kinds of literature, such as melanoma [ 33 ], ovarian cancer [ 34 ], gastric cancer [ 35 ], pancreatic ductal adenocarcinoma [ 36 , 37 ], and colon cancer [ 38 ]. In our study, KLK6 is validated as an independent and unfavorable prognostic factor of BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry analysis of tissue sections of ovarian and melanoma patients found the overexpression of KLK6 in tumor associated stromal cells and keratinocytes (72,73). In pancreatic ductal adenocarcinoma, immunostaining analysis of epithelial tumor cells and the surrounding stroma and immune cells showed that high KLK6 protein levels in the tumor and immune cells are significantly associated with shorter survival compared to low protein levels (74). mRNA analysis of colorectal cancer (CRC) tissue samples from 136 patients showed upregulated KLK10 expression (75).…”
Section: Kallikrein Related Peptidases (Klks)mentioning
confidence: 99%